2021
DOI: 10.1371/journal.pone.0257405
|View full text |Cite
|
Sign up to set email alerts
|

Impact of herpes zoster vaccination on incident dementia: A retrospective study in two patient cohorts

Abstract: Background Herpes zoster (HZ) infection increases dementia risk, but it is not known if herpes zoster vaccination is associated with lower risk for dementia. We determined if HZ vaccination, compared to no HZ vaccination, is associated with lower risk for incident dementia. Methods and findings Data was obtained from Veterans Health Affairs (VHA) medical records (10/1/2008–9/30/2019) with replication in MarketScan® commercial and Medicare claims (1/1/2009-12/31/2018). Eligible patients were ≥65 years of age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 27 publications
4
39
1
Order By: Relevance
“…In the current study, we found no attenuation of the association between vaccinations and incident dementia after adjusting for tetanus, diptheria, pertussis, or HZ infection that could have onset between index and end of follow‐up. This is consistent with our previous research indicating post‐vaccination HZ infection does not moderate the association between HZ vaccination and incident dementia 35 . The current results, taken together with the number of different vaccinations linked to lower dementia incidence and findings related to HZ vaccination, lead us to suspect a nonspecific mechanism.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, we found no attenuation of the association between vaccinations and incident dementia after adjusting for tetanus, diptheria, pertussis, or HZ infection that could have onset between index and end of follow‐up. This is consistent with our previous research indicating post‐vaccination HZ infection does not moderate the association between HZ vaccination and incident dementia 35 . The current results, taken together with the number of different vaccinations linked to lower dementia incidence and findings related to HZ vaccination, lead us to suspect a nonspecific mechanism.…”
Section: Discussionsupporting
confidence: 93%
“…11 Although some evidence indicates age group differences in the relationship between HZ vaccination and risk for dementia, current findings are inconsistent across data sets. 35 Further research is needed to confirm these findings and overcome limitations of our retrospective cohort design. Although a randomized controlled trial (RCT) could be informative, it may be too difficult to detect incident dementia using sample sizes and follow-up time in typical RCTs.…”
Section: Limitationsmentioning
confidence: 93%
“…A total of 17 studies involving 1857,134 participants assessed the association between common vaccinations and subsequent risk of dementia ( 19 24 , 32 43 ). All included studies were population-based studies with sample sizes ranging from 1290 to 551344.…”
Section: Resultsmentioning
confidence: 99%
“…A previous meta-analysis has found a significantly lower risk of dementia after influenza vaccination, but this study did not further explore the factors that might influence this association ( 18 ). In addition, several studies have examined the association between various other common vaccines, such as shingles, diphtheria, and tetanus vaccines, and the risk of dementia ( 19 24 ). Nevertheless, the current evidence on the association between vaccination and dementia risk is inconsistent and there is a lack of studies that have comprehensively explored this topic, so we conducted this meta-analysis and systematic review to investigate the effect of different vaccinations on dementia risk, taking into account the influence of age, sex, and dose.…”
Section: Introductionmentioning
confidence: 99%
“…After controlling for confounders, the researchers found a 46-53% reduction in AD among patients who had received Tdap. A similar study was undertaken to investigate an association between herpes zoster (HZ) vaccination and dementia [43]. Compared with no HZ vaccination, HZ vaccination resulted in a 31-35% risk reduction in dementia and a 25-30% risk reduction in AD.…”
Section: Discussionmentioning
confidence: 99%